High-efficiency green and red phosphors enable a broader hue-gamut light-emitting diode backlight for brighter displays - Dieu An Nguyen Thi; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
In this article, we suggest combining a blue InGaN chip with strait-band green (β-sialon:Eu2+), red (K2SiF6:Mn4+) phosphors to create WLED devices with a wide hue range and high effectiveness that may be utilized in LCD backlighting. The highest radiation wavelength of a gas-pressure sintedβ-sialon:Eu2+ is 535 nm, the full width at half maximum (FWHM) is 54 nm, and the outside quantum performance is 54.0% lower than the 450 nm stimulation. We created K2SiF6:Mn4+ in two steps. The phosphor possesses a sharp line radiation spectrum accompanied by the most intense maximum point under 631 nm, an FWHM reaching roughly 3 nm, as well as an exterior quantum effectiveness of 54.5%. When computed at 120 mA, the manufactured three-range wLEDs had an illuminating performance of 91–96 lm/W and a large color temperature of 11,184–13,769 K (i.e., 7,828–8,611 K in LCD screens). The hue range represented by the CIE 1931 and CIE 1976 hue gaps is 85.5-85.9% and 94.3-96.2% of the NTSC requirement, respectively. The optic characteristics outperform those of phosphor-transformed wLED backlights utilizing broad-range green or red phosphors, indicating the two strait-range phosphors studied are the best luminous substances for producing brighter and livelier screens.